Nilai Moral dalam Novel Catétan Poéan Réré Karya Ai Koraliati - Bayu Wahyudin; Ruhaliah Ruhaliah; Agus Suherman (JENTERA: Jurnal Kajian Sastra, 2025)
This study examines the narrative structure and moral values in the novel Catétan Poéan Réré by Ai Koraliati, a contemporary Sundanese literary work that boldly addresses LGBTQ+ issues, particularly gender identity and sexual orientation (Lesbian, Gay, Bisexual, Transgender, and Queer/Questioning), within a society that upholds religious norms, propriety, and social harmony. The study employs a qualitative descriptive method with content analysis techniques to identify forms of moral values, classified according to Sudaryat’s framework, which includes human relationships with God, the self, others, nature, time, and the pursuit of both physical and spiritual well-being. The analysis reveals that all six categories of moral values are manifested explicitly and implicitly through the narrative, dialogues, and character actions. The novel presents emotional dynamics, moral conflicts, and reflective processes experienced by the characters as they face social pressures and questions of identity. Beyond its strong narrative structure, the work conveys profound ethical messages without being didactic. Catétan Poéan Réré illustrates how literature can serve as a space for dialectical engagement between traditional values and the complexities of contemporary Sundanese social realities. Abstrak Penelitian ini mengkaji struktur naratif dan nilai-nilai moral dalam novel Catetan Poéan Réré karya Ai Koraliati, sebuah karya sastra Sunda kontemporer yang secara berani mengangkat Isu LGBTQ+ merujuk pada identitas gender dan orientasi seksual (Lesbian, Gay, Biseksual, Transgender, dan Queer/Questioning) yang ada dalam masyarakat yang menjunjung tinggi norma agama, kesopanan, dan harmoni sosial. Penelitian ini menggunakan metode deskriptif kualitatif dengan teknik analisis isi untuk mengidentifikasi bentuk-bentuk nilai moral yang diklasifikasikan oleh Sudaryat, yaitu hubungan manusia dengan Tuhan, diri sendiri, sesama manusia, alam, waktu, serta dalam meraih kebahagiaan lahiriah dan batiniah. Hasil analisis menunjukkan bahwa keenam kategori nilai tersebut terwujud dalam narasi, dialog, dan tindakan tokoh secara eksplisit maupun implisit. Novel ini menampilkan dinamika emosional, konflik moral, serta proses reflektif tokoh-tokohnya dalam menghadapi tekanan sosial dan identitas. Selain menyuguhkan struktur cerita yang kuat, karya ini juga menyisipkan pesan-pesan etis yang dalam, tanpa kesan menggurui. Catetan Poéan Réré memperlihatkan bahwa sastra dapat menjadi ruang dialektika antara nilai-nilai tradisional dan kompleksitas realitas sosial kontemporer masyarakat Sunda.